Sustentabilidade da região metropolitana de Belém-Pará sob a ótica de diferentes índices - PEREIRA, Fabiana da Silva (2017)
In the Amazon more than 70% of the population lives in urban areas. Its urbanization is recent and has occurred in an accelerated way, which has caused a series of socioeconomic and environmental problems, deepening even more the regional disparities. The metropolitan region of Belém (RMB) is a second largest metropolitan area of the Amazon and it concentrates almost a third of the state population. The RMB presents a series of infrastructure and environmental problems that influence sustainability. Currently, there are several methodologies for measuring sustainability, however, a lot still needs to be learned about the ideal system to be applied in certain contexts and scales. In this way, the present work aimed to analyze the sustainability of the metropolitan area of Belém by application of different indexes, an aim to know the degree of sustainability of the municipalities that compose this region, and also to test different indexes in the same unit of analysis. Three systems of sustainability indexes were applied: Urban Sustainability Indexes System - SISU, Barometer of Sustainability – BS and Dashboard of Sustainability - PS. The results show that there is inequality in the sustainability indexes of municipalities of RMB, whose results were better applied to Belém. The application of the SISU showed little variation in the Index of Environmental Quality - IQA and Municipal Human Development Index - IDHM, and in relation to the Institutional Political Capacity - ICP that this metropolis presents a greater intermunicipal inequality that demonstrates a need of institutional and political strengthening of the region. The application of BS and PS shows that the municipality of Belém, followed by Ananindeua, has a better level of sustainability than the other municipalities in the surrounding area. The three systems present some distortions in relation to the ranking of municipalities. These distortions can be mainly related to the way in which results are interpolated and how the indices are indicated, whether synthetically or not. Although the results for the municipality of Belém presented a better performance, the intra-municipal evaluation showed that there is a great inequality within the municipality. The most central areas have the best results. On the other hand, the peripheral areas presented unsatisfactory results, mainly in relation to urban environmental conditions, infrastructure and sanitation. These results show that in addition to evaluation at the municipal level, evaluation at the intramunicipal level is necessary, since the municipal averages hide the existing inequalities.